147 Effectiveness of operator protection devices to mitigate injuries associated with quad-bike (ATV) rollovers. (1st September 2016) - Hicks, David; Grzebieta, Raphael; Boufous, Soufiane; Rechnitzer, George; Robertson, David; Simmons, Keith
Abstract : Background: There is growing concern regarding the number of serious injuries and fatalities related to quad bikes (All-Terrain Vehicle or ATV) in many countries of the world related to the farming sector. There have been over 150 quad bike fatalities in Australia since 2000, many of which involve the rider losing control at a low speed with the vehicle subsequently rolling on top of the rider and crushing or asphyxiating them. Operator Protection Devices (OPDs) developed in Australia and New Zealand are designed to reduce the potential of such incidents. Manufacturers, however, claim that OPDs have the potential to increase the incidence of injuries and deaths during a rollover event. Currently, there are around 3000 OPDs fitted to quad bikes in Australia and are now being sold in the USA. Methods: 300 farmers and other users who have a Quadbar OPD fitted to their quad bike will be surveyed about the performance of the quadbar in a rollover event. Participants will be asked about their quad bike usage patterns and history of rollover events before and after the fitment of a Quadbar. Participants will be interviewed face to face and via telephone. Results: Information on rider demographics, usage for work (mustering, carrying loads, transporting, etc.) and other purposes (recreational), terrain over which the quad bikes are ridden, direct information relating to incidents involving quad bikes with and without an OPD, injuries resulting from an OPD, and other safety relevant information, will be collected. Conclusions: The study will provide real world recorded evidence determining whether indeed the injury risk when using an OPD on a quad bike (ATV) increases or instead reduces crush related injury and asphyxia fatality potential and related to purpose of task.